Effects of perinatal period administration of clomiphene citrate in sexual behavior, organ weights and hormone concentration of Wistar male and female rats - Oliani, Andrea Lucia Natali; Dias, Lilian Mara Kirsch; Naves, Jeanete Lopes; Bernardi, Maria Martha; Oliveira, Claudio Alvarenga (Brazilian Journal of Veterinary Research and Animal Science, 2015)
The effects of prenatal exposure to clomiphene citrate in sexual behavior, organ weight and hormone concentrations of male and female rats was evaluated. The animals received four doses of clomiphene citrate 2 mg/mL each during the prenatal period (21 days of gestation – DG21) on days 1 (DN1), 2 (DN2) and 3 (DN3) after the birth of the puppies. The treatment led to the development of polycystic ovaries in 70% of the females, masculinization of female sexual behavior and changes in sexual behavior of males evidenced by the reduction in the number of ejaculations. In regards to hormone levels, a decrease in the FSH levels in male offspring was observed. It was concluded that clomiphene citrate interferes with the reproductive capacity of male and female rats and female sexual orientation when prenatally administered.